Are 100% Green Composites and Green Thermoplastics the New Materials for the Future? - Jean Marc Saiter; Larisa Dobircau; Nathalie Leblanc (International Journal of Polymer Science)
A review of the history of the evolution of material science and material technology shows us that one tendency for the future could be the use of agriculture resources. In this work, we review the performances of one of these resources, that is, wheat flour. We show that it is possible to get thermoplastic films with properties quasiequivalent to what is obtained for expensive pure starch. By adding natural fibres, composites are also obtained. These composites exhibit performances which allow their use only for short duration.